Enhanced textural properties of milk-low acyl gellan dual gels by exogenous calcium - Jing Wang; Zuguo Chen; Xi Shu; Yijiao Zou; Xueke Chen; Weibo Zhang; Chong Chen (Applied Food Research)
Designing milk protein-hydrocolloids based composite gels is widely accepted strategy to enhance the yogurt texture and stability in the dairy industry. In this study, whole milk and low acyl gellan (LAG) were used to form double network gels induced by acid and fortified Ca2+, and their textural properties and sensory properties were investigated. The water holding capacity and firmness of acid gels significantly increased from 56.9%, 17.1 g to 89.8%, 272.6 g, respectively, after forming milk/LAG dual gels. The addition of calcium citrate further increased these two textural properties of dual gels. Compared with single milk gels and dual gels, the Ca2+ fortified dual gels showed more regular and denser double gel network structure with the highest storage modulus. This study indicated that Ca2+ fortification could enhance the textural properties of milk-LAG double gels, showing huge potential for dairy industry.